Anteseden Loyalitas Konsumen Pengguna Jamsostek Mobile Application (JMO) Terhadap Persepsi Citra Merek, Kepuasan Konsumen Dan Kepercayaan: Aplikasi Teori SOR - Meta Riani Siahaan; Rifelly Dewi Astuti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the antecedents of consumer loyalty to users of the Jamsostek Mobile (JMO) application by applying the Stimulus – Organism – Response (SOR) theory. Data as many as 500 respondents users of the Jamsostek Mobile Application (JMO are processed using the SmartPLS application version 3. The results show that the perception of service quality, brand image perception, and customer satisfaction have a significant positive effect on customer loyalty instead with trust. Citra brand perception and customer satisfaction are also able to mediate the influence of service quality on customer loyalty. The brand image perception variable, trust and customer satisfaction can act as an organism that supports customer responses in the form of loyalty.